(untitled) (Journal of the College of Education for Women, 2019)
Importance of the research:The importance of any educational or scientific research through its intellectual arena of facts supply the individual and society, Supports Knowledge and Science Group, which raised will be locked in these topics in the future.This research seeks to shed light on the image and the role of women and men in the books of the Arabic language in primary education (primary), To illustrate the negative effects of the phenomenon of sexism in textbooks, And its negative impact on emerging, And stay away as much as possible about the distinction between the sexes in the roles and qualities in textbooks traditional stereotypes and remove that put both sexes templates hinder the development of the individual and the limit of its capabilities and ambitions, And impede the march and progress of society. (Hormuz.1988).The difference between the sexes is based on a patriarchal culture and the world of organized by men for men is the reason for this gender discrimination, Despite the progress made by women in the fields of life. (Lutfi, 1988).If we go back to the real reason for the gender discrimination we are seeing is due to the composition of the social system in the Arab countries are biased stereotypes, It is necessary to point out that the roles played by women has undergone many profound changes as a result of the rapid cultural change in the present era. (Shriha’a, 1989).Research Objectives:The current research aims to:1- The role and image of women and men in the Arabic language books in primary education in the Republic of Iraq characterization2-Identification of the positive roles of women in these books.3-Identify negative roles that emerged by women.Search ProceduresSampleArabic language teachers in primary schools affiliated to the Directorate of Educational Karkh third place in Baghdad, Where was their number (166) teacher.Search toolWas drafted resolution for the study analysis of reading books at the elementary level, Where the number of questions (35) Question arranged within three alternatives respectively [ Ok, I dunno, Is Ok], Mark has been under what is appropriate of the three alternatives at the discretion of the Arabic language teacher verified or unverified.Statistical methods1. The questions were arranged in descending order according to the resolution percentile weight for each question where2. The number of occurrences of unloading answer at every level of the three resolution levels.3. dish Kay law for each question in the questionnaire to calculate the calculated value and compare the value tabular.Search ResultsThrough content analysis of reading books at the elementary level and compatibility with the results of the questionnaire, The results can be summarized as follows:- There are significant differences between the books directed toward males and females and their orientation towards the percentages were clearest evidence of this.- There is a difference and disparity between male and female attendance at these textbooks in favor of men as Danh and Statistics.- The results showed a significant impact practiced textbooks enshrining sexism process through traditional stereotypical references inherited impose values and standards of society and culture.- There is a disparity between the number of authors and works, technicians and professionals, scientists and processes, in these books for the benefit of men.- There is a disparity between the number of poets and poets of poems books in favor of men.- There is a disparity in the female and male audience, As a secondary female characters, The male pivotal and key often in favor of men.- There is a disparity between the images and fees earmarked for females and males, The difference is also in favor of men.